Answer:
[tex]x=\dfrac{D}{1+\sqrt{\dfrac{m}{M}}}[/tex]
Explanation:
Mass of moon = m
Mass of planet =M
We know that gravitational force given as
[tex]F=G\dfrac{m_1m_2}{d^2}[/tex]
[tex]F'=G\dfrac{m'M}{x^2}[/tex]
[tex]F=G\dfrac{m'm}{(D-x)^2}[/tex]
Given that force is zero so
F=F'
[tex]G\dfrac{m'm}{(D-x)^2}=G\dfrac{m'M}{x^2}[/tex]
[tex]\dfrac{m}{(D-x)^2}=\dfrac{M}{x^2}[/tex]
[tex]\dfrac{x}{D-x}=\sqrt{\dfrac{M}{m}}[/tex]
[tex]\dfrac{D-x}{x}=\sqrt{\dfrac{m}{M}}[/tex]
[tex]x=\dfrac{D}{1+\sqrt{\dfrac{m}{M}}}[/tex]